Two-base DNA hairpin-loop structures in vivo. - Davison, A (1994)
In vitro studies have revealed that DNA hairpin-loops usually contain four unpaired bases. However, a small subset of sequences can form two-base loops. We have previously described an in vivo assay that is sensitive to tight loop formation and have set out to test whether DNA sequences known to form two-base loops in vitro also form tight loops in vivo. It is shown that the sequences 5'dCNNG and 5'dTNNA behave as predicted if they favour two-base loop formation in vivo, a result that is consistent with previously described in vitro studies. The ability of specific DNA sequences to form tight loops in vivo has implications for their potential to form transient structures involved in gene regulation, recombination and mutagenesis.